Trait Response to Nitrogen and Salinity in Rhizophora mangle Propagules and Variation by Maternal Family and Population of Origin - Richards, Christina L.; Langanke, Kristen L.; Mounger, Jeannie; Fox, Gordon A.; Lewis, David B. (Frontiers in Marine Science, 2021)
Many coastal foundation plant species thrive across a range of environmental conditions, often displaying dramatic phenotypic variation in response to environmental variation. We characterized the response of propagules from six populations of the foundation species Rhizophora mangle L. to full factorial combinations of two levels of salinity (15 ppt and 45 ppt) reflecting the range of salinity measured in the field populations, and two levels of nitrogen (N; no addition and amended at approximately 3 mg N per pot each week) equivalent to comparing ambient N to a rate of addition of 75 kg per hectare per year. The response to increasing salinity included significant changes, i.e., phenotypic plasticity, in succulence and root to shoot biomass allocation. Propagules also showed plasticity in maximum photosynthetic rate and root to shoot allocation in response to N amendment, but the responses depended on the level of salinity and varied by population of origin. In addition, propagules from different populations and maternal families within populations differed in survival and all traits measured except photosynthesis. Variation in phenotypes, phenotypic plasticity and propagule survival within and among R. mangle populations may contribute to adaptation to a complex mosaic of environmental conditions and response to climate change.